Quality Work and the Moral Economy of European Employment Policy. (27th October 2015) - Bolton, Sharon; Laaser, Knut; Mcguire, Darren
Abstract: Following a decade of radical economic and workplace restructuring, it is important to understand how state employment policies support or deny human flourishing. This article utilizes a realist document analysis approach and reviews European employment policy through a moral economy lens. It fuses different moral economy approaches, drawing together the work of Karl Polanyi and Andrew Sayer a multi‐layered conceptual lens is offered that explores the tensions between a commodification of labour and human needs. A dominant market ideology is revealed, highlighting how quality work has been subsumed by the flexicurity agenda in the EU.